Hubungan Tingkat Pengetahuan dan Sikap Ibu dengan Pemberian Alat Bermain Pada Anak Usia Toddler di Wilayah Kerja Puskesmas Ulak Karang Kota Padang - Erni Musmiler; Ira Sri Budiarti; Wulan Oktarina (Jurnal Amanah Kesehatan, 2022)
The World Health Organization (WHO) states that the percentage of deaths from non-communicable diseases is 63% compared to infectious diseases. Indonesia based on the results of hypertension occurs in the elderly age group (55.2%). West Sumatra more. Patients with hypertension at the age of 60 years and over are around 650,000 people (19.1%). The highest incidence of hypertension in the elderly was found at the Air Cold Health Center, Padang, which ranked first as many as 920 people (38.5%). The purpose of this study was to determine the relationship between family support and adherence to hypertension treatment in the elderly at the Air Cold Padang Public Health Center in 2022. This type of research is quantitative with a cross sectional design. The study was carried out in February – September 2022. Data collection was on 22 – 27 August 2022. The population in this study were all hypertensive elderly who came to visit the Padang Air Cold Health Center totaling 154 people with a sample of 61 people. The sampling technique is accidental sampling. The study used a questionnaire by means of interviews. Data were analyzed by univariate and bivariate using Chi-Square statistical test with a significance level of 95% = 0.05. The results showed that less than half of 44.3% had elderly medication adherence. Less than half of 45.9% have low knowledge. More than half 50.8% have poor motivation in the elderly, more than half 52.5% have unsupportive families in the elderly. There is a relationship between the level of knowledge, motivation, family support and adherence to treatment for hypertension in the Air Cold Padang Public Health Center in 2022. Factors level of knowledge, motivation, family support associated with adherence to treatment of hypertension elderly. It is expected that health workers will further improve providing information to patients with hypertension in compliance with treatment according to the schedule by health workers. The conclusion of this study is that it is expected that health workers will improve providing information to patients with hypertension in adherence to treatment as scheduled by health workers.